I may talk in English but gaali toh Hindi mein hi denge: A study of English-Hindi Code-Switching and Swearing Pattern on Social Networks - Grover, Jeenu; Agarwal, Prabhat; Sharma, Ashish; Sikka, Mayank; Rudra, Koustav; Choudhury, Monojit (Proceedings of the Social Networking Workshop, COMSNETS 2017, 2017)
Social networking has changed the way people communicate. Online social networks (OSNs) support information and resource sharing, aid discovery of globally dispersed individuals, and even enable measurement of research impact. Several novel applications, diverse access interfaces, and a large economic system has developed around OSNs. Going past simple characterization of social media, the community has shown significant interest in addressing various research problems associated with the field. This workshop strives to bring together academia and industry to present developments on both research and engineering challenges associated with social networks.